Alzheimer's polygenic hazard score in SuperAgers: SuperGenes or SuperResilience?. Issue 1 (2nd August 2022) - Spencer, Barbara E.; Banks, Sarah J.; Dale, Anders M.; Brewer, James B.; Makowski‐Woidan, Beth; Weintraub, Sandra; Mesulam, M.‐Marsel; Geula, Changiz; Rogalski, Emily
Abstract: Introduction: SuperAgers are individuals over age 80 with superior episodic memory, at a level consistent with individuals 20 to 30 years their junior and who seem to show resistance to age‐related neurofibrillary degeneration. Here we examine whether low genetic risk for Alzheimer's disease (AD) contributes to SuperAgers' unusually high episodic memory performance in advanced age. Methods: The AD polygenic hazard score (PHS) was calculated for each SuperAger and cognitively normal participant and compared between groups. Results: A total of 37 SuperAgers (73% female, mean [standard deviation] 82.7 [2.8] years old) and 35 controls (54% female, 83.7 [4.3] years old) were included. There was no significant difference in the AD PHS between SuperAgers and cognitively normal controls. Discussion: Unusually successful cognitive aging cannot be simply explained by low polygenic risk for AD as assessed by common genetic variants. However, rare variants and common protective genetic factors may contribute to resistance or resilience. Highlights: SuperAging cannot be simply explained by low polygenic risk for Alzheimer's disease. Rare variants and common protective genetic factors may contribute to SuperAging. A protective factors polygenic score may uncover mechanisms for SuperAging.